INFORMATION GAP ACTIVITIES IN LESSON STUDY FOR TEACHING ENGLISH FOR YOUNG LEARNERS (TEYL) CLASS - Paulina Paulina (Universitas Muhammadiyah Gresik, 2015)
This study was conducted in order to know the implementation of Information gapactivities in Teaching English for Young Learners class. These activities were designedthrough lesson study. Lesson study aimed to improve the quality of teaching learning whichconsists of three stages, plan, do, see. Through the first plan, information gap activitieswere chosen as the supporting activities to help students comprehend the basic principlesand theory about teaching English for Young Learners. These activities required students towork in group and transfer the information they had after they were asked to read thematerials given. The activities were conducted through four cycles of Lesson Study whichrequired four lecturers to be involved, one as the model teacher and the rests are observers.Through the lesson study, the information gap activities could be monitored through dostage and reflected through the see stage which resulted in students comprehension in basicprinciple and theory about teaching English for Young Learners. Thus, the result can beeffectively lead to students' ability in designing and implementing the teaching learning ofEnglish for Young Learners